IMPLEMENTASI KONSEP KELUARGA SAKINAH PADA KALANGAN KELUARGA DIFABEL (STUDI KASUS DI KELURAHAN BAKALANKRAJAN KECAMATAN SUKUN KOTA MALANG) - Wulan Nur Diana; Khoirul Asfiyak; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
different from most families, for couples with disabilities who have physical limitations that can be an obstacle to carrying out activities in general, it is possible that they are able to live happily at home for years, thus giving rise to the aim of research to describe Families with Disabilities in Understanding Family Concepts. Sakinah and to describe the Efforts of Families with Disabilities in Forming Sakinah Families This study uses a descriptive qualitative approach, the type of research is case study, data collection techniques use non-participant observation, and structured interviews, the data sources of this study were obtained from 3 couples with disabilities in Bangkalankrajan Village, Sukun District, Malang City. The results of the study show that families with disabilities in understanding the concept of a sakinah family are happy families, patient with each other, understanding and supporting each otherIn realizing a sakinah family, the three couples with disabilities strive together to maintain good communication between members so as to minimize quarrels in the household, families provide support to each family member, understand each other''s conditions, help each other, try to patient and work together in educating children in goodKata kunci: Implementation, Couple, Sakinah Family, Disability